A phospho-harmonic orchestra plays the NLRP3 score - Bornancin, Frédéric; Dekker, Carien (Frontiers in Immunology, 2023)
NLRP3 is a prototypical sensor protein connecting cellular stress to pro-inflammatory signaling.A complex array of regulatory steps is required to switch NLRP3 from an inactive state into a primed entity that is poised to assemble an inflammasome. Accumulating evidence suggests that post-translational mechanisms are critical. In particular, phosphorylation/dephosphorylation and ubiquitylation/deubiquitylation reactions have been reported to regulate NLRP3. Taken individually, several post-translational modifications appear to be essential. However, it remains difficult to understand how they may be coordinated, whether there is a unique sequence of regulatory steps accounting for the functional maturation of NLRP3, or whether the sequence is subject to variations depending on cell type, the stimulus, and other parameters such as the cellular context. This review will focus on the regulation of the NLRP3 inflammasome by phosphorylation and dephosphorylation, and on kinases and phosphatases that have been reported to modulate NLRP3 activity. The aim is to try to integrate the current understanding and highlight potential gaps for further studies.